LEARNING ISLAM IN A MODERATE WAY: HOW PESANTREN TEACHES ISLAMIC VALUES AND NATIONHOOD TOWARD SANTRI? - Suprapto Suprapto (Jurnal Sosiologi Reflektif, 2022)
The 9/11 tragedy has brought up negative stereotype to pesantren identified as a radical Islamic educational institution in Indonesia. In April 2022, BNPT (National Counterterrorism Agency) released 198 Islamic boarding schools which affiliated with radicalism. The increasing cases of intolerant acts in Indonesia have been exacerbating the relations among religious communities. This study intends to analyze the roles of two Islamic boarding schools, that are Al-Hikmah and Roudhotut Tholibin, in Indonesia, in producing moderate values of Islam to their students. This study employs a qualitative approach through a case study. Data were collected by observing various activities in the two Islamic boarding schools, FGD, and in-depth interviews with ten informants. The findings showed that Pesantren Al-Hikmah and Pesantren Roudhotut Tholibin taught moderate values of Islam, primarily through the teaching process of the classical book entitled Idhotun  Nasyi'in. It provides students with social aspects of interaction with non-Muslims and the values of differences. In doing so, students are also invited to participate in community activities to exercise the values of nationalism in Islamic boarding schools. This research further indicates that pesantren is not a place where radicalism grows but it has become an Islamic educational institution that can produce moderation and national values.Peristiwa terorisme 9/11 silam telah menyisakan stereotype negatif pada pesantren sebagai lembaga pendidikan Islam yang radikal di Indonesia. Pada April 2022 lalu, BNPT (Badan Nasional Penanggulangan Terorisme) telah merilis 198 pesantren yang terafiliasi dengan radikalisme. Hal ini diperburuk oleh data kasus intoleransi di Indonesia yang meningkat. Penelitian ini bermaksud untuk menganalisis dua pesantren yakni Al Hikmah dan Roudhotut Tholibin di Indonesia dalam peranannya memproduksi nilai-nilai moderat dalam berislam kepada para santri. Penelitian dilakukan dengan pendekatan kualitatif melalui studi kasus. Data dikumpulkan melalui observasi berbagai kegiatan di dua pesantren tersebut, FGD, dan wawancara mendalam terhadap 10 informan santri. Hasil penelitian menunjukkan bahwa Pesantren Al Hikmah dan Pesanten Roudhotut Tholibin justru mengajarkan nilai-nilai moderat dalam berislam, khususnya melalui pengajaran kitab klasik Idhotun Nasyi’in. Kitab-kitab beserta dengan tafsir yang diajarkan kepada santri sarat dengan  ajaran-ajakan bagaimana berinteraksi secara baik dengan non-muslim dan kelompok yang berbeda. Santri juga diajak berpartisipasi dalam kegiatan di masyarakat sehingga mampu menumbuhkan benih-benih nasionalisme di pesantren. Penelitian ini selanjutnya menajdi indikasi kuat bahwa pesantren bukanlah tempat tumbuhnya radikalisme, namun justru telah menjadi lembaga pendidikan Islam yang mampu memproduksi nilai moderat dan nilai kebangsaan.